2018
DOI: 10.5539/elt.v11n8p51
|View full text |Cite
|
Sign up to set email alerts
|

Free Voluntary Reading: Promoting Vocabulary Learning and Self-Directedness

Abstract: This action research study focuses on measuring the impact of a Free Voluntary Reading Program on students' active vocabulary use and self-direction in language learning in two different programs of English as a foreign language. The impetus for this research came from close observation and a needs analysis that confirmed students' reluctant attitude towards reading, due to deficiency in vocabulary, as well as the limited access to books of their interest in the target language. The implementation of the progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…More importantly, in the contemporary context of global radical technological advancement, language competency is the major tool for learners to adapt to the unprecedented changes and master necessary skills for the 21st century world [7][8][9]. Studies have suggested that avid readers have higher propensity for critical thinking [10] and self-direction skills [11], which are associated with more self-awareness, clearer life goals and higher achievements in adulthood [12]. Reading proficiency has also been found to be the predicting factor for academic performance, including Science, Technology, Engineering and Mathematics (STEM) subjects, as well as educational attainment at secondary level [13,14].…”
Section: A Brief Overviewmentioning
confidence: 99%
“…More importantly, in the contemporary context of global radical technological advancement, language competency is the major tool for learners to adapt to the unprecedented changes and master necessary skills for the 21st century world [7][8][9]. Studies have suggested that avid readers have higher propensity for critical thinking [10] and self-direction skills [11], which are associated with more self-awareness, clearer life goals and higher achievements in adulthood [12]. Reading proficiency has also been found to be the predicting factor for academic performance, including Science, Technology, Engineering and Mathematics (STEM) subjects, as well as educational attainment at secondary level [13,14].…”
Section: A Brief Overviewmentioning
confidence: 99%
“…While some studies reported improved reading rate and reading comprehension (Suk, 2016;McLean & Rouault, 2017;Tran, 2018), others suggest that ER did not improve students' reading comprehension (Shih, 2015;Azmuddin et al, 2019). ER's positive impact on vocabulary gains was more consistently found in studies (Suk, 2016;Bautista & Marulanda, 2018;Tan & Kasuma, 2019;Tan et al, 2018), however, Boutorwick et al (2019 noted that learners need to be interested or engaged for ER to improve their vocabulary knowledge. Studies discussed in this paper also seem to suggest that ER has a positive impact on ESL/EFL reading motivation (Ro, 2013;Bautista & Marulanda, 2018;Tan & Kasuma, 2019).…”
Section: Discussionmentioning
confidence: 94%
“…Recent studies were also in line with Liu and Zhang's (2018) findings that ER helps with vocabulary acquisition. Bautista and Marulanda's (2018) study on university students in two private universities in Colombia revealed that the free voluntary reading programme implemented with vocabulary-learning instruction improved active vocabulary use and retention. Suk (2016) also found that the treatment group that experienced ER performed better than the control group in vocabulary tests.…”
Section: Impact Of Er On Vocabulary Knowledgementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, learners have also been known to like books that are more difficult if they find the content more meaningful (Chiu, 2015). Bautista and Marulanda's (2018) study to investigate whether a free voluntary reading programme could affect students' interest in reading and reading frequency also found that after the intervention there was an increase of 62% of students with improved attitude toward voluntary reading. In a study conducted in a Malaysian public university, remedial English language learners who experienced Sustained Independent Reading (SIR) indicated that they felt more motivated to read in English (Tan & Kasuma, 2019).…”
Section: Impact Of Extensive Reading On Esl Reading Motivationmentioning
confidence: 99%